Kebijakan Redaksional MQTV Bandung dalam Penyiaran Berita - Adib Darissalam (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2017)
The religious life is experiencing rapid development in conjunction with the revolutionary changes in the media. At the stage of modernization, entered the twentieth century, the development of the media is an industry with a wide range of cultures that make it up. But when the religious interests collide with culture media system, there was friction that easily trigger sensitivity. Harmonization of religion and culture media, which never happened in the centuries to write the media triumph, now it is often disturbed and provoked by the dynamics posed by culture media. In the context of the relationship between religion and culture of this media, one major question that deserves to be answered in this paper is; how to bridge the interests of religion (as something divine, sacred and ceremonial) with the media culture as an industrial capitalist. What implications arise and which will result from this relationship. Will a positive effect on the religious or otherwise.